Pengaruh Perbandingan Mocaf (Modified Cassava Flour) Dan Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Flakes - Sembiring, Delvi; Wisaniyasa, Ni Wayan; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
This study was aiming to determine the effect comparison of mocaf and red bean sprout flour on the characteristics of flakes and find out the best comparison of mocaf and red bean sprout flour to obtain the best characteristics of the flakes. The experimental used completely randomized design with the comparison of mocaf and red bean sprout flour as a treatment which consists of 5 levels: 100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%. The treatment was repeated three times, resulting in 15 experimental units. The data obtained were analyzed using an analysis of variance and if the treatment had a significant effect, it was followed by a Duncan Multiple Range Test (DMRT). The results showed that the comparison of mocaf and red bean sprout flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, endurance time crispness in milk, hedonic test of colour, aroma, texture, taste, and overall acceptance and scoring test of colour and texture. Flakes from comparison of 80% mocaf and 20% red bean sprout flour had the best characteristics, with a water content 2.35%, ash content 2.90%, protein content 8.40%, fat content 4.96%, carbohydrate content 81.38%, crude fiber content 4.38% and endurance time crispness in milk for 2.38 minutes, the color was cream and liked, the aroma liked, the texture was crispy and liked, the taste liked, and overall acceptance liked.